Damages and causative factors of 2015 strong Nepal Earthquake and directional movements of infrastructures in the Kathmandu Basin and along the Araniko Highway - S. Manandhar; T. Hino; S. Soralump; M. Francis (International Association of Lowland Technology, 2016)
The strong earthquake on April 25, 2015 (7.8 Mw) and the aftershock on May 12, 2015 (7.3 Mw) claimed the lives of 8,659 people, plus 21,150 people injured and huge economic loss together with serious damages on eight World Heritage sites. Our two field surveys in the month of from May 9-21, 2015 and 19-23 July, 2015 revealed understanding of damages to traditional towns, historical monuments, and modern buildings. Regionally, damages on buildings are confined to the traditional houses which are remnants of or renovated after the 8.1 magnitude 1934 AD earthquake. Widespread cases of inadequate engineering and construction practices for RCC (Reinforced Cement Concrete) buildings and renovated old buildings have been severely affected. The affected region includes the main shock along the 150 km long rupture zone towards east. The aftershock reached farther south at a shallower depth towards the end of the eastern rupture zone. As a result damages inflicted in the structures from both quakes revealed different shaking directions. The April 25 main shock caused eastward leaning structures while May 12 aftershock caused southward leaning and/collapsed structures. It is important to identify whether the direction is due to aftershock at the end of initial rupture zone or if it represents a newly exposed fault.